Organizational support that is aware of the work motivations of technical staff in the sports and scouting activity departments of the Baghdad/Karkh Directorates General of Education - Ismail, Asst.Prof.Dr.Shatha Abdel Hafez (Sulaimani Journal for Humanities, 2025)
This research aimed to determine the perceived organizational support for the work motivations of technical supervisors in the sports and scouting departments of the Baghdad Al-Karkh Education Directorates, specifically focusing on the following dimensions: political and administrative motivations, interpersonal motivations, incentive motivations, and self-actualization motivations. It also aimed to determine the level of perceived organizational support for these work motivations within the sports and scouting departments of the first, second, and third Baghdad Al-Karkh Education Directorates. To achieve this objective, the descriptive-analytical method was employed, and a questionnaire was designed as the primary data collection tool. The research sample consisted of 70 technical supervisors from the sports and scouting departments within the Baghdad Al-Karkh Education Directorates. The data were analyzed using the SPSS statistical software. Based on the results, several conclusions and recommendations were formulated. The most important conclusion was that the dimension of "organizational support for self-actualization motivation" ranked first in the need for organizational support, with the statement "job stability and its positive effects on the performance of the technical supervisor" receiving the highest mean and percentage. The most important recommendation is to implement immediate feedback on the achievements of technical supervisors and their performance levels, as this satisfies their need for achievement motivation.
Keywords: Perceived organizational support; motivation